Critical review of Shariah screening guidelines for Islamic equity market - Htay, Sheila Nu Nu (s.n, 2012)
This research is undertaken to critically analyze the current Shariah screening norms and to examine the Shariah tenets and basis of Shariah screening practice significantly and identify the underlying causes contributing to diverse stipulations and opinions. The researcher believes that the finding of the study will contribute to the enhancement of Shariah screening practice and will foster the sustainable growth of Islamic equity market